Epitaxial growth of insulating and superconducting monolayers of (BETS)2GaCl4 on Ag(111). Issue 11 (7th October 2015) - Hassanien, Abdou; Zhou, Biao; Tanaka, Hisashi; Miyazaki, Akira; Tokumoto, Madoka; Kobayashi, Akiko; Zupanič, Erik; Muševič, Igor
Abstract : The ability to fabricate crystalline monolayers of confined superconducting or magnetic condensate on surfaces is a key issue to realize new functionalities and understand the nature of competing orders in their phase diagram at the nanoscale. Herein, we outline a reliable method to pattern a monolayer of superconducting islands and Kagome lattice of (BETS)2 GaCl4 (where BETS = bis(ethylenedithio) tetraselenafulvalene) on Ag(111). At a deposition temperature of 125 K, (BETS)2 GaCl4 dimers form Kagome lattice with a pore size of 1.2 nm, making it possible to encapsulate small molecules within the nanoporous network. When deposited at 300 K, the molecules retain their superconducting structure and minimize substrate interaction by aligning their long molecular axis perpendicular to the substrate. These results provide guidelines for facile controllable fabrications of epitaxial superconducting and/or magnetic confined condensates on metal surfaces.